THE PROBLEM OF LONELINESS IN OLD AGE AND STRATEGIES FOR OVERCOMING IT - Sitora Akbarovna Ikromova (Prospects for innovative technologies in science and education, 2025)
Loneliness in old age is a multifaceted psychological and social phenomenon that can significantly affect the overall well-being, mental health, and physical condition of older adults. While aging is often accompanied by changes such as retirement, loss of loved ones, and declining health, these factors may contribute to the reduction of social networks and the emergence of chronic loneliness. This article examines the causes, consequences, and coping strategies for loneliness in late life, drawing on research in gerontology, psychology, and public health. It analyzes the interplay between social isolation, emotional well-being, and health outcomes, and highlights evidence-based interventions, including social engagement programs, psychological counseling, digital communication tools, and community support systems. Emphasis is placed on the importance of creating inclusive and supportive environments that foster social connections and enhance the quality of life for older individuals.